2002
DOI: 10.1590/s0021-75572002000300008
|View full text |Cite
|
Sign up to set email alerts
|

Importância da avaliação oftalmológica em recém-natos

Abstract: This study showed that many ocular disorders presented at birth are not noticed by pediatricians (56%), which highlights the importance of ophthalmological evaluation in all newborns as a routine examination in the first 48 hours of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
3
0
2
Order By: Relevance
“…These results were then grouped into four categories, It should also be noted in Table 2, that the sample of this study was composed primarily of full term NBs (direct ophthalmoscopy), showed that the main ocular alteration found through the test was opacity of the cornea (14) .…”
Section: Methodsmentioning
confidence: 94%
“…These results were then grouped into four categories, It should also be noted in Table 2, that the sample of this study was composed primarily of full term NBs (direct ophthalmoscopy), showed that the main ocular alteration found through the test was opacity of the cornea (14) .…”
Section: Methodsmentioning
confidence: 94%
“…Li et al 19 performed RetCam evaluation on 14,786 individuals and identified eye alterations in 2% (excluding cases of retinal hemorrhage), including treatable retinal diseases, 11 cases of congenital cataract, three cases of retinoblastoma, in addition to eye abnormalities that may be associated with systemic diseases such as microphthalmia and congenital optic nerve anomalies. Wasilewski et al, 20 in a prospective study in which ophthalmologists evaluated 667 NBs in the maternity ward, identified ocular alterations in 25 (3.75%). It is noteworthy that in 56% of patients with altered ophthalmologic examination, the pediatrician did not identify any abnormality on the routine examination.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, severe alterations were confirmed in four (3.33% of suspected cases and 0.03% of total NBs), a result close to that found in the Italian study, 15 but with the identification of considerably fewer severe cases when compared to reports of global ophthalmologic evaluation, most of them performed with a RetCam. 18 , 19 , 20 …”
Section: Discussionmentioning
confidence: 99%
“…6 A realização do teste já constitui rotina obrigatória em algumas localidades dos estados do Rio de Janeiro, São Paulo, Minas Gerais e Santa Catarina, regulamentada por meio de Projetos de Lei. [6][7] Esse exame, também conhecido como "teste do olhinho", é rápido, simples e realizado com o auxílio de um oftalmoscópio direto, preferencialmente com o ambiente em penumbra.…”
Section: Ingrid Martins Leite Lúcio 3 Islane Castro Verçosaunclassified